Relationship between Social Media Access and Adolescent Reproductive Health Behavior in SMK Banyumas Regency - Lestari, Devi Intan; Ningrum , Ema Wahyu; Safitri, Maya (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Adolescents face poor reproductive health behavior due to low literacy and access to relevant health information even though social media has the potential as a source of information. The study aims to analyze the relationship between social media access and adolescent reproductive health behavior. This research method is quantitative with a cross-sectional approach. Sampling technique with proportionate random sampling as many as 290 students of SMK Tujuh Lima 1 Purwokerto and SMK Ma'arif NU 2 Ajibarang class X and XI. The research instrument is online through google form. The social media access questionnaire has been tested for validity and reliability with a Pearson value of 0.334 and Cronbach alpha of 0.750. The results of this study showed that the majority of respondents in SMK Kabupaten Banyumas were 16 years old (49%), female (60%), and other sources for accessing reproductive health information used electronic media (22%). Most had less social media access (54%) but good reproductive health behavior (91%). There was a weak relationship between social media access and reproductive health behavior (p-value 0.001, r = 0.188). These findings suggest to further strengthen reproductive health education through social media that is interesting and relevant to adolescents